Curcuma lampangensis and C. sabhasrii, two new species of the family Zingiberaceae from northern Thailand - SARAYUT RAKARCHA; SURAPON SAENSOUK; CHARUN MAKNOI; MATHEE WONGNAK; WORANART THAMMARONG; PIYAPORN SAENSOUK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rakarcha S, Saensouk S, Maknoi C, Wongnak M, Thammarong W, Saensouk P. 2022. Curcuma lampangensis and C. sabhasrii, two new species of the family Zingiberaceae from northern Thailand. Biodiversitas 23: 4448-4459. Curcuma lampangensis Saensouk, Maknoi & Rakarcha and C. sabhasrii Saensouk, Maknoi, Wongnak & Rakarcha, two new species of ginger family (Zingiberaceae) from northern Thailand, are described, illustrated and photographed. Additionally, the authors provide their detailed morphological descriptions, as well as illustrations, color photographs, distributions, ecology, etymology, phenology, vernacular, conservation status and its closely related species. The two new species are assignable to the Curcuma subgenus Ecomatae. Curcuma lampangensis and C. sabhasrii are endemic to Lampang and Phitsanulok provinces of northern Thailand, respectively. The morphological characteristics of C. lampangensis are compared to C. rhomba J. Mood & K. Larsen while C. sabhasrii is compared to C. peramoena Souvann. & Maknoi. Curcuma lampangensis is recognized by its glabrous on nearly all parts of the plant, creeping rhizome and the inflorescence usually arises from a new rhizome branch next to the existing pseudostem, flowers that are white to pale pink and white to pale yellow labellum with 2 dark yellow bands at the center and reddish tinge at the base. Curcuma sabhasrii is recognized by having 8-15 greenish to reddish-purple bracts, reddish-purple corolla lobes, white with reddish-purple mottling to reddish-purple staminodes and labellum which is reddish-purple with an embossed yellow path along the midrib from base to apex and reddish-purple mottling on yellow mid-band of lower half. A key to 24 species of Curcuma subgenus Ecomatae in Thailand is presented.